Testing traditions in cycling: newspapers are effective thermal insulators during simulated downhill cycling - Beal, H.; Goodall, S.; Modhwadia, A.; Barwood, M. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: Cycling downhill accelerates heat loss and requires lower work rates leading to cold discomfort. Historically, cyclists have behaviorally thermoregulated prior to cycling downhill by inserting newspapers into their jerseys. Yet, there is no experimental data to support such a method showing improvements in thermal perception and profile; we hypothesized it would. METHODS: Two cohorts (N=8 each) of male participants completed two main trials each involving 30-minutes simulated uphill cycling (65% VO2peak 188 [41] W; no fan) followed by 15-minutes downhill cycling (35% VO2peak 41 [12] W) in front of an industrial fan (wind speed: 4.6 [0.1] m/s). In one trial participants inserted one (study 1) or two (study 2) tabloid newspapers into their jerseys (PAPER) prior to downhill cycling; the other was a control (NOPAPER). Whole body and torso thermal sensation (TS) and comfort (TC), aural temperature (Tau), skin temperature (Tskin), and newspaper mass change (Delta) were measured. Data were compared using ANOVA and t-test to 0.05 alpha level. RESULTS: After uphill cycling thermal and perceptual profiles were similar. In study 1, only TC was transiently improved 1-minute after newspaper insertion. In study 2, Tskin rate of decline was lower in the PAPER condition (-0.11 [0.12] °C/min; cf -0.53 [0.16] °C/min; P=0.001) and Tchest remained higher (28.83 [3.17] °C cf 24.39 [3.22] °C). This improved TS but not TC. Newspaper mass increased indicating impaired sweat evaporation (Delta mass: 5.7 [4.9] g; P=0.01). CONCLUSIONS: Thermal perception and profile during downhill cycling was improved by inserting two newspapers but not one newspaper into the jersey, supporting our hypothesis.